A study on the effectiveness of speed hump as a speed reducer in residential area / Mohd Zulkarnain Abdul Manan - Abdul Manan, Mohd Zulkarnain (2004)
One of the most important of traffic calming systems is the reduction of traffic speed, fast driving, inconsiderate towards other road users and selfishness are the root to the occurrence of most road traffic accidents in Malaysia. Many traffic calming devices such as speed humps, speed breaker, textured pavement will increase motorist's awareness and forced them to reduce their vehicular speeds. The popular 3 T's (Engineering. Education and Enforcement) approaches are implemented by the authorities, but the results are much more to be desired. Our local authorities have had experiences on certain traffic calming devices such as speed humps, speed breaker, speed tables, textured pavements, transverse bar and others but no records or studies done on their effectiveness. The speed hump was effective in reducing traffic speeds when the device is properly installed. Speed humps are a geometric roadway design feature with the purpose of slowing traffic in residential area. The speed hump also reduced the number of vehicles exceeding the speed limit in the immediate vicinity of the devices. Speed humps should be placed so that vehicles do not approach at high speeds. Speed humps should not be placed on curves, transit routes, or major emergency response routes. When designed and installed properly, speed humps will reduce vehicle speeds to 24-32 kph at the hump and 40-48 kph between humps in a series.